Carotenoid and molecular markerbased diversity assessment in tropical yellow endosperm maize inbred lines - Adeyemo, O. Sarah; Menkir, A.; Gedil, Melaku A; Omidiji, O. (2011)
Maize is a staple food crop for many people in Africa where millions of children, pregnant women and nursing mothers suffer from vitamin A deficiency. The β-carotene found in yellow maize can be used as a primary source of provitamin A. Several tropical yellow endosperm maize inbred lines with varying carotenoid concentrations have been identified as potential parents for breeding. Diversity assessment of these inbred lines was conducted using 17 AFLP primer combinations, 87 SSR markers and carotenoid composition to identify parents for making crosses to develop new inbred lines with high provitamin A carotenoids. Genetic distance (GD) values among all pairs of inbred lines varied from 0.08 to 0.64 with an average of 0.48 for AFLPs, and from 0.007 to 0.59 with an average of 0.45 for SSRs. The Euclidean distances calculated from carotenoid composition of the lines varied from 0.30 to 9.00 with an average of 3.27. Cluster and principal coordinate analyses based on AFLP and SSR-based GD estimates separated the lines into grouping consistent with their pedigrees. Although the correlations of molecular marker-based clustering with carotenoid-based clustering were not strong, molecular analysis could be used as the basis to identify diverse lines with complementary carotenoid compositions as parents for making bi-parental crosses to increase the level of provitamin A in tropical maize. The GD estimates can also be used as the basis to select yellow endosperm maize inbred lines for broadening and diversifying the genetic base of sources of provitamin A carotenoids in tropical yellow endosperm maize germplasm.